Asset returns under model uncertainty: evidence from the euro area, the U.S. and the U.K. - Jo\~ao Sousa; Ricardo M. Sousa (European Central Bank (ECB), 2013)
The goal of this paper is to analyze predictability of future asset returns in the context of model uncertainty. Using data for the euro area, the US and the U.K., we show that one can improve the forecasts of stock returns using a model averaging approach, and there is a large amount of model uncertainty. The empirical evidence for the euro area suggests that several macroeconomic, …financial and macro-financial variables are consistently among the most prominent determinants of the risk premium. As for the US, only a few predictors play an important role. In the case of the UK, future stock returns are better forecast by …financial variables.
Keywords: E21; G11; E44; 330; Bayesian model averaging; Model uncertainty; Stock returns